16S rDNA analysis of archaea indicates dominance of Methanobacterium and high abundance of Methanomassiliicoccaceae in rumen of Nili-Ravi buffalo. (October 2015) - Paul, S.S.; Deb, S.M.; Dey, A.; Somvanshi, S.P.S.; Singh, D.; Rathore, R.; Stiverson, J.
Abstract: The molecular diversity of rumen methanogens was investigated using 16S rDNA gene library prepared from the rumen contents of Nili-Ravi buffaloes. Microbial genomic DNA was isolated from four adult male fistulated buffaloes and PCR conditions were set up using specific primers. Amplified product was cloned into a suitable vector, and the inserts of positive clones were sequenced. A total of 142 clones were examined, and the analysis revealed 46 species level (0.01 distance) operational taxonomic units (OTUs). Twenty six OTUs comprising 89 clones (63% of the total clones) were taxonomically assigned to Methanobacterium genus and the majority of them had highest percent identity with Methanobacterium flexile among cultured methanogens. Five OTUs comprising 27 clones (19% of total clones) were taxonomically assigned to Methanomicrobium genus and these clones showed highest sequence identity with Methanomicrobium mobile . Only two OTUs comprising 6 clones (4% of total clones) were assigned to Methanobrevibacter genus. A total of 17 clones belonging to 10 species level OTUs showed highest percent identity (ranging from 85 to 95%) with Methanomassilicoccus luminyensis and were taxonomically classified as Methanomassiliicocaceae . Out of the 142 rDNA clones, 112 clones, which constitute 79% of the total clones representing 42 OTUs, had less than 98.5% sequence identity with any of the cultured strains of methanogens and represent novel species of methanogens. This study has revealed the largest assortment of hydrogenotrophic methanogen phylotypes ever identified from the rumen of Nili-Ravi buffaloes. The study indicates that Methanobacterium is the most dominant methanogen in the rumen of Nili-Ravi buffalo. This is also the first report on the presence of methanogens phylogenetically close to M. luminyensis, an H2 dependent methylotrophic methanogen, in the rumen of buffaloes at such a high level of abundance. Highlights: Largest assortment of methanogen phylotypes identified from Nili-Ravi buffaloes. Methanobacterium is the most dominant methanogen in rumen of Nili-Ravi buffalo. Abundance of Methanomassiliicoccacae in rumen of buffalo shown for the first time. Archaeal community in Nili-Ravi buffaloes are different from other breeds or cattle. This study hints at strategy for mitigation of CH4 emission from Nili-Ravi buffaloes.